2016
DOI: 10.1186/s12884-016-0913-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with postnatal care utilisation in Rwanda: A secondary analysis of 2010 Demographic and Health Survey data

Abstract: BackgroundPostnatal care (PNC) in the first seven days is important for preventing morbidity and mortality in mothers and new-borns. Sub-Saharan African countries, which account for 62 % of maternal deaths globally, have made major efforts to increase PNC utilisation, but utilisation rates remains low even in countries like Rwanda where PNC services are universally available for free. This study identifies key socio-economic and demographic factors associated with PNC utilisation in Rwanda to inform improved P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 20 publications
(21 reference statements)
11
46
2
Order By: Relevance
“…The higher tendency of PNC utilization by employed mothers might be due to mothers who are involved in paid employment are more likely to be economically independent and consequently have access to services, and utilize the services when they need or as recommended by their health workers [25]. Evidence showed that having a paid job empowers mothers to utilize maternal health services [26, 29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…The higher tendency of PNC utilization by employed mothers might be due to mothers who are involved in paid employment are more likely to be economically independent and consequently have access to services, and utilize the services when they need or as recommended by their health workers [25]. Evidence showed that having a paid job empowers mothers to utilize maternal health services [26, 29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…1). Women who delivered at home were the interest of this analysis for PNC service use because women who delivered at health facility were more likely to receive postnatal care even though the care was likely to be initiated by health care providers and thus does not measure women’s health seeking behavior [29–32].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…From these mothers, 1,055 who delivered at home were studied to identify factors associated with receiving postnatal care ( Figure 2). We focused on women who delivered at home because women who deliver at a health facility are more likely to receive postnatal care, which is initiated by health care providers and thus does not measure women's health seeking behavior [63][64][65][66].…”
Section: Datamentioning
confidence: 99%